Auditory brainstem implant in postlingual postmeningitic patients. (20th October 2015) - Bayazit, Yildirim; Kosaner, Julie; Celenk, Fatih; Somdas, Mehmet; Yilmaz, Ismail; Altin, Gokhan; Cevizci, Rasit; Yavuz, Haluk; Ozluoglu, Levent
Abstract : Objectives/Hypothesis: The aim of this study was to evaluate outcomes of postlingual postmeningitic patients who received an auditory brainstem implant (ABI). Study Design: Retrospective analysis was performed on postlingual postmeningitic patients with bilateral profound sensorineural hearing loss who underwent ABI between the years 2007 and 2014 Methods: All patients were postlingually deaf due to cochlear ossification as a consequence of bacterial meningitis. The patients received a MED‐EL or Neurelec ABI. All patients were operated on at different hospitals by the same primary surgeon. The patients were tested using Ling 5 sound detection, sound field implant thresholds between 250 Hz and 6 kHz, and 6 to 12 choice closed‐set word and sentence tests. Results: Nine patients with postmeningitic cochlear ossification received an ABI. Five of nine ABI users (55.5%) wear their audio processors (AP) most of the time. Four (44.5%) with no perceivable benefit have become nonusers. Three of the five consistent ABI users reported good benefit. The other two ABI users who do wear their APs do not respond to sound in daily living but reported benefits such as "feeling sound" in a good way. Conclusions: In this study, five of nine patients (55.5%) with bilateral ossified cochlea had some degree of benefit from their ABI. An ABI may be useful in hearing restoration in postlingual patients with bilateral ossified cochlea due to meningitis. However, poor results may be related to side effects, which may necessitate deactivation of electrodes, long duration of auditory deprivation, or impairments in the auditory neural structures as a result of meningitis. Level of Evidence: 4. Laryngoscope, 126:1889–1892, 2016